Application of raman spectroscopy in the non-invasive diagnosis of urological diseases via urine - Ailiyaer Ainiwaer; ShuWen Sun; Ayinuer Bohetiyaer; Yuchao Liu; Yufeng Jiang; Wentao Zhang; JingCheng Zhang; Tianyuan Xu; Hanyang Chen; Xudong Yao; Chengyou Jia; Yang Yan (Photodiagnosis and Photodynamic Therapy)
Objectives: The objective of this review is to provide a comprehensive overview of the utilization of Raman spectroscopy in urinary system diseases, highlighting its potential in non-invasive diagnostic methodologies for early diagnosis and prognostic assessment of urinary ailments. Methods: We searched PubMed, Web of Science, and Google Scholar using 'raman,' 'bladder,' 'kidney,' 'prostate,' 'cancer,' 'infection,' 'stone or urinary calculi,' and 'urine or urinary,' along with 'AND' and 'OR' to refine our search. We excluded irrelevant articles and screened potential ones based on titles and abstracts before assessing the full texts for relevance and quality. Findings: The findings indicate that RS can furnish data on biomolecules in urine, which is significant for non-invasive diagnostic approaches. It has shown potential within non-invasive diagnostic methodologies and is expected to play a pivotal role in the early diagnosis and prognostic assessment of urinary system diseases, such as malignancies, urinary tract infections, kidney diseases, urolithiasis, and other urinary conditions. Conclusions: Raman spectroscopy has demonstrated significant potential in providing precise and rapid diagnostic approaches for clinical use in the context of urinary system diseases. Its ability to analyze biomolecules non-invasively positions it as an increasingly important tool in the early diagnosis and prognostic assessment of these conditions.